PERBEDAAN HASIL BELAJAR KOGNITIF MAHASISWA BIOLOGI YANG MENGGUNAKAN MODEL PEMBELAJARAN INKUIRI DAN GROUP INVESTIGATION - Rita Fitriani (Jurusan Pendidikan Biologi - Universitas Siliwangi, 2016)
The study aimed to determine the differences in cognitive learning result of biology students using inquiry and group investigation on the concept of biodevisersity. The research was comparative descriptive with one group pretest-postest design. Learning data collection techniques using pretest and posttest form and data were analyzed using independent t test. The result showed that there were differences in the biology students of learning result who use models of inquiry and group investigation and based on n-gain analysis know that inquiry learning model gives better results than group investigation.